Health Education Program for Children in Godog Village-Garut As A Preventive Effort to the COVID-19 Virus - Nopi Rantika; Shilpa Fitria; Kharisma Putri N; Deska Syiami; Dina Mulyani (Fakultas Kewirausahaan Universitas Garut, 2020)
An epidemic of an acute respiratory disease called COVID-19 occurred at the end of 2019 in Wuhan (China) which spread throughout the world. COVID -19 can affect everyone from adults, the elderly, and children. So there needs to be education that is easy to carry out about Covid-19 and how to prevent it. This is the basis of the problem in encouraging community service activities so that they can be active in efforts to prevent COVID-19. The purpose of this educational activity is to prevent the spread of Covid-19 which is increasingly happening in Indonesia, so it is hoped that adults and children can take Covid-19 prevention. The method used during this activity is in the form of offline and online education to the surrounding community, where the material presented is in the form of proper handwashing and how to make hand sanitizers. As a result of the educational activities that have been carried out, there has been a significant change in the habits of the surrounding community where children can wash their hands properly and correctly, and for adults, especially local mothers can make hand sanitizers with the right natural ingredients to be used as emergency hand sanitizers. in daily activities.